Designing English Reading Text Based On Traditional Wedding Rituals from Java Island - Gressensia, Angela; Claudia, Sarah; Sihombing, Maria; Laia, Astika; Br Tarigan, Merry Susanty; Mahendra, Made Wahyu (English Language Teaching Prima Journal (ELT), 2022)
Students’ interest in reading comprehension was affected by the source of texts at the school. Student have low ability in reading comprehension because the students did not have various reading textbooks. The limitation of English reading book sources had affected the students’ motivation in learning English, especially in reading comprehension. Many students were not interested in reading comprehension bacause they thought that it was really boring. In according to overcome these problems faced by the students at school, this research aims to develop Folklore in Traditional Wedding Rituals from Java Island and how to How to design English reading text based on folklore in traditional wedding rituals from Jawa island. This research was conducted by applying qualitative descriptive method. The writers took the data by interviewing a cultural practicioner (Mr. M.S.), classified as an interviewee in this research. The writers interviewed a person who had understood weel about Traditional Wedding Rituals from Java Island, especially from central of Java. From the data it was known that there were some traditional wedding rituals from Java islan, such us Balangan Gantal, Wijikan, Pondongan or Kanten Asto, Tampa Kaya, Dahar Gembul, Ngunjuk Rujak Degan, Mapag Besan and Sungkeman. The writers designed English reading text based on folklore in traditional wedding rituals from Jawa island by preparing questions to the cultural practicioner, choosing the appropriate practiconer, discussing with the cultural practicioner, conducting interview to the cultural practicioner, writing down the interview result, translating the texts into English reading text, revising it, and finally it became an Englsih reading text that could be used by the English teachers and students. The data collection was done by reading the interview result, then they were made to be an English reading text. After carrying out this research, it can be conluded that folklore in traditional wedding rituals from Jawa island can increase the students’ interest in reading comprehension class and the students could get more motivation in joining the class.